Study of government regulation number 48 2008 concerning education funding - Elfianawati, Nilla; Rahmat, Pupu Saeful (Enrichment : Journal of Management, 2023)
Finance and funds are resources that directly support the effectiveness and efficiency of education delivery. Schools must be able to plan, implement, evaluate, and be accountable. This study uses literature studies in order to gain a comprehensive understanding of the research topic. The constitutional value guarantee for education funding is Article 31 (2) UUD 1945, Law No. 49 of 2003, Law No. 34 of 2003, and Law No. 20 of 2003. The state is responsible for financing education by dividing the education budget into APBN (Anggaran Pendapatan dan Belanja Negara) and APBD (Anggaran Pendapatan dan Belanja Daerah). Education financing policies are determined on the basis of fairness, decency and the principle of continuity. Those responsible for education financing are: the government and local government, the community or educational units of parents and assistance activated from other parties. Education financing policies are determined on the basis of fairness, decency and the principle of continuity.